The Influence of Academic Service Quality on Student Loyalty: Mediating Effects of Student Satisfaction - Fakhrudin, Arif; Nuryakin, Nuryakin; Fatmawati , Indah; Suyanto , M. (UPT Publikasi Ilmiah UNISBA, 2025)
This study aims to analyze the effect of academic service quality on student loyalty and explore the role of student satisfaction as a mediating variable in this relationship. Specifically, this study seeks to identify the extent to which academic service quality can increase student loyalty directly or indirectly through student satisfaction. The method used in this study is path analysis. The data used are quantitative data collected through a survey using a questionnaire. The research sample consisted of 100 students undergraduate from various study programs at Yogyakarta Aerospace Technology College selected using convenience sampling techniques. Data processing and analysis were carried out using AMOS software to test the relationship between variables in the research model. The results of the study indicate that academic service quality has a positive and significant effect on student satisfaction, which in turn affects student loyalty. Student satisfaction is proven to be a mediating variable that strengthens the relationship between academic service quality and student loyalty. This finding emphasizes the importance of improving academic service quality in building student loyalty in higher education environments.